The Model Development of a Family Capacity Building for Adolescent Pregnancy Prevention in Nakhon Phanom Province - Kata, Wisai; Somkumlung, Patchanee; Mangkarakeree, Nutcharat (Journal of The Royal Thai Army Nurses, 2020)
The purposes of this research were 1) to develop model of a Family Capacity building for Adolescent pregnancy prevention in Nakhon Phanom province 2) to evaluate model of a Family Capacity building for Adolescent pregnancy prevention in Nakhon Phanom province. The research procedure consisted of four phases including : context analysis, developing the model testing and evaluating of the model. The results were as follows: 1. The model development of a Family Capacity building for Adolescent pregnancy prevention in Nakhon Phanom province called APPLE Model consisted of 5 factors: Assessment, Problem Lists, Purpose, Level of activities and Effective Evaluation. 2. The result of model development of a Family Capacity building for Adolescent pregnancy prevention in Nakhon Phanom province showed that the overall was at a high level satisfaction ( = 4.72, S.D. = .57). When classifying into the Ease of use, Suitability, The completeness of the information, Performance / speed.